HUBUNGAN TEKANAN PANAS DENGAN TEKANAN DARAH PADA PEKERJA PERPARKIRAN KENDARAAN BERMOTOR DI BASEMENT PLAZA CENTER POINT MEDAN TAHUN 2015 - amita shintiar; halinda sari lubis; umi salmah (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT More of the companies did not pay attention to the environment physical condition of the worker in parking area, while basement has not sufficient ventilation and there are any parked vehicles that cause the increasing of temperature in the basement area The method of research is an analytic survey with cross sectional design. The sample is 30 of 40 population by purposive sampling; the measurement of temperature in work area in basement using questtemp by technician who have operate the tools previously. And the blood pressure is measured using digital tension meter OMRON by paramedic.. Based on the results of research indicates that during 3 days, the average of temperature is 28.95 C. The higher temperature is 29.54 C. The lower temperature is 28.63 C on Sunday. The average of systolic blood pressure before take work is 121 mmHg and the average of diastolic blood pressure before take work is 81 mmHg, while the average of systolic blood preasure after to take work is 133 mmHg and the average of diastolic blood pressure after to take work is 89 mmHg. this indicates that there is increasing of blood pressure before and after to take work. There is a correlation between the temperature and the increasing of blood pressure to the parking operator in the basement Plaza Center Point Medan 2015 (p = 0.001). It is suggested to the workers should be consuming water while being served and use the rest time effectively on the fresh area both in operator’s room and outside the basement and also do not smoke. So that workers want to consume water, the company should prepare and obiges workers to drink. If possible the company should put up the exhaust fan